Nucleoside diphosphate kinase B deficiency causes a diabetes-like vascular pathology via up-regulation of endothelial angiopoietin-2 in the retina - Qiu, Yi; Bauer, Alexander; Schneider, Stefan W.; Hammes, Hans-Peter; Wieland, Thomas; Feng, Yuxi (Acta diabetologica, 2016)
Aims: Nucleoside diphosphate kinase B (NDPKB) is capable of maintaining the cellular nucleotide triphosphate pools. It might therefore supply UTP for the formation of UDP-GlcNAc from glucose. As NDPKB contributes to vascular dysfunction, we speculate that NDPKB might play a role in microangiopathies, such as diabetic retinopathy (DR). Therefore, we investigated the impact of NDPKB on retinal vascular damage using NDPKB-/- mice during development of DR and its possible mechanisms. Methods: Pericyte loss and acellular capillary (AC) formation were assessed in streptozotocin-induced diabetic NDPKB-/- and wild-type (WT) mice. Expression of angiopoietin-2 (Ang2) and protein N-acetylglucosamine modification (GlcNAcylation) were assessed by western blot and/or immunofluorescence in the diabetic retinas as well as in endothelial cells depleted of NDPKB by siRNA and stimulated with high glucose. Results: Similar to diabetic WT retinas, non-diabetic NDPKB-/- retinas showed a significant decrease in pericyte coverage in comparison with non-diabetic WT retinas. Hyperglycemia further aggravates pericyte loss in diabetic NDPKB-/- retinas. AC formation was detected in the diabetic NDPKB-/- retinas. Similar to hyperglycemia, NDPKB deficiency induced Ang2 expression and protein GlcNAcylation that were not further altered in the diabetic retinas. In cultured endothelial cells, stimulation with high glucose and NDPKB depletion comparably increased Ang2 expression and protein GlcNAcylation. Conclusions: Our data identify NDPKB as a protective factor in the retina, which controls Ang2 expression and the hexosamine pathway. NDPKB-deficient mice are a suitable model for studying mechanisms underlying diabetic retinal vascular damage.